2007
DOI: 10.1097/mbc.0b013e3280116c36
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro efficacy of different platelet glycoprotein IIb/IIIa antagonists and thrombolytics on platelet/fibrin-mediated clot dynamics in human whole blood using thrombelastography

Abstract: Suppressing platelet activation improves efficacy of thrombolytic therapy for stroke and acute myocardial infarction. Combination treatment with recombinant tissue plasminogen activator (r-tPA) and glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitor that binds with high affinity to platelets may therefore improve the efficacy of thrombolytic therapy. The effect of platelet GPIIb/IIIa antagonists and/or r-tPA on the dynamics of platelet/fibrin clot formation, strength, and lysis was determined using thrombelastography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, low levels of FXIII [26] or excessive fibrinolysis may be associated with reduced MCF [27]. Finally, inhibition of glycoprotein IIb/IIIa receptors diminishes the MCF [28]. In the present study, the most likely explanation for reduced MCF was reduced level of fibrinogen.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, low levels of FXIII [26] or excessive fibrinolysis may be associated with reduced MCF [27]. Finally, inhibition of glycoprotein IIb/IIIa receptors diminishes the MCF [28]. In the present study, the most likely explanation for reduced MCF was reduced level of fibrinogen.…”
Section: Discussionmentioning
confidence: 69%
“…21 In vitro and in vivo experimental studies suggest that combination therapy (fibrinolytic agent plus GPIIB/IIIA inhibitor) provide more complete lysis than fibrinolytics alone. 22, 23 The combination was evaluated in a multicenter phase 2 study, The Combined Approach to Lysis Utilizing Eptifibatide and tPA in Acute (CLEAR trial). 24 Ninety-four 0–3 hour ischemic stroke patients were randomized into 3 different arms: IV-tPA (0.9mg/kg) alone or two different combination arms of low-dose IV-tPA (0.3mg/kg and 0.45mg/kg)+eptifibatide (75 μg/kg bolus followed by 0.75μg/kg/minute infusion for 2 hours) with combination treatment given in 69 patients (3:1 randomization to combination arms).…”
Section: Combined Pharmacological Approaches (Lytic + Antithrombotic mentioning
confidence: 99%
“…The MCF remained unaffected by increasing concentrations of phospholipids, and similar to observations gained from other experimental conditions the amplitude was independent of the type and concentration of activator. [7], the effect of vasoactive agents, platelet agonists, and anticoagulants [22,23], as well as assessment of storage of donor platelets [24]. Some studies have revealed that different types of activators provide different results in various clinical scenarios, such as e.g.…”
Section: Phospholipid Titration Studies (Figure 3 Panel A-c)mentioning
confidence: 99%